Praktik Pengelolaan Limbah Industri Dalam Perspektif Maqasid Syari’ah - Suci Suryawati (El-Faqih : Jurnal Pemikiran dan Hukum Islam, 2022)
The existence of an industry is very synonymous with the presence of waste. Waste if disposed of carelessly will cause pollution to the environment and will affect human health. Therefore, to avoid pollution, management is needed to minimize the impact of the waste. As well as the management carried out by tapioca flour producers in Kaliboto Village, Tarokan, Kediri, although management efforts have been carried out, there is still pollution found. Based on these problems, the focus of this research is how waste management practices in the tapioca flour home industry of Kaliboto Village, Tarokan District, Kediri Regency in the perspective of maqasid syari'ah. This research is a case study using a qualitative approach. The primary data source in this study is the results of observations and interviews with tapioca flour home industry managers, village governments and local communities. The result of this study is that there are several efforts that have been appropriate or not in accordance with the value of shari'ah maqasid. First, from the value of hifdz an-nafs that have been appropriate, namely maintaining health by increasing the productivity of livestock through feeding that contains high nutrition and meets the needs of life by managing waste. The management that is not yet appropriate is the lack of maximum management of liquid waste so that it can endanger yourself and others. Second, from the value of hifdz al-mal, namely obtaining property in a good way through waste management so that it can get additional income and open new businesses.